STUDY ON ASHES OF BLENDED COAL-BIOMASS FOR CO-FIRING SYSTEM IN A COAL FIRED BOILER - Ikin Sodikin; Datin Fatia Umar (Puslitbang tekMIRA, 2013)
Biomass and coal blend combustion or co-firing is a promising combustion technology. However, significant development work is required before large-scale implementation can be realized. Issues related to successful implementation of coal biomass co-firing mainly for power generation should be identified. This paper presents the results of the study on blended coal-biomass characterisation, particularly the ash chemical composition and ash fusion temperature to predict the slagging and fouling propensity in a coal fired boiler. The coal used in this research has a calorific value of 5,067 cal/g and the ash fusion temperature of softening temperature in oxidation condition (softening temperature-ox) is 1,228ºC, while the biomass used was baggase, straw and rice husk with the calorific value of 4,144; 3,545; 3,301 cal/g and the softening temperature-ox of 1,303; 1,420 and >1,500ºC, respectively. Experimental results for some varieties of fuel blends indicate that the proportion of 95%-5% of coal and baggase has the highest softening temperature-ox of 1,225ºC. The blend of coal and straw resulted in the highest softening temperature-ox of 1,240ºC at 95%-5%, while the blend of coal and rice husk, the highest softening temperature-ox of 1,235ºC was reached at the proportion of coal and rice husk at 90%-10%. According to the slagging and fouling index, blended coal and straw shows the best performance compared to that of blended coal either with baggase or rice husk